1.66 CXCL4 and CXCL7 expression on macrophages: a potential predictor of disease outcome in patients presenting with early synovitis?. (31st January 2014) - Adlard, Nichola J; Yeo, Lorraine; Hardie, Deborah L; Adams, Holly; Juarez, Maria; Buckley, Christopher D; Raza, Karim; Filer, Andrew; Scheel-Toellner, Dagmar
Abstract : Background and Objectives: Within the context of a comprehensive study of the pathology of the early stages of rheumatoid arthritis (RA) we compared cytokine mRNA expression in the synovium of patients with early inflammatory arthritis who later progressed to rheumatoid arthritis with that of patients with a resolving disease course. Interestingly, we found a trend towards higher expression of platelet related chemokines CXCL4 and CXCL7 mRNA in early RA synovium. We therefore investigated CXCL4 and CXCL7 expression at the protein level and its co-localisation with platelets, macrophages and blood vessels. Methods: Synovial tissue biopsies were obtained from treatment naïve patients presenting with at least one clinically swollen joint within the first 12 weeks of symptom onset. Patients who went on to develop RA (according to the 1987 ACR criteria) at an 18 month follow-up (n = 8), as well as patients whose arthritis spontaneously resolved (n = 9) were included. In addition, biopsies collected from longer duration (> 12 weeks) treatment naïve RA patients (n = 10) and patients with mechanical symptoms undergoing knee arthroscopy without obvious signs of inflammation were included as controls (n = 7). Synovial tissue sections were stained with antibodies specific to CXCL4 or CXCL7, CD41, CD68 and vWF using immunofluorescence and staining was quantified using Zeiss imaging software. Specificity of CXCL7 staining was confirmed by blocking with recombinant cytokine. Results: We observed a statistically significant increase of CXCL4 and CXCL7 protein expression in patients with early RA when compared to early resolvers (CXCL4 p = 0.036, CXCL7 p = 0.011). This increase reflected a transient stage of early disease, as in treatment-naïve patients with more than 12 weeks disease duration the expression level of these chemokines was found at levels comparable to non-inflamed synovium. Both CXCL4 and CXCL7 co-localised with blood vessels, platelets and CD68 + macrophages within the synovial tissue. However, only staining found outside blood vessels, which co-localised largely with CD68 as a marker for macrophages, differed between synovium from patients with resolving, early and established arthritis (CXCL4 p = 0.063, CXCL7 p = 0.028). Conclusions: We have identified two chemokines, CXCL4 and CXCL7, that are expressed at higher levels on macrophages during a transient phase in early RA. Future work will investigate whether these chemokines play a role in disease progression and/or may be used as biomarkers for prediction of disease outcome.